2012
DOI: 10.5171/2012.459427
|View full text |Cite
|
Sign up to set email alerts
|

The Triple Bottom Line Effect on Emerging Market Companies: A Test of Corporate Social Responsibility and Firm Value Relationship

Abstract: Over the last twenty years, after corporations have historically focused their reporting systems on the provision of financial information needed by managers and shareholders to assess risks and calculate returns, the global awareness of the need to assess the full spectrum of corporate value has grown dramatically. The triple bottom line or total returns on capital-economic, social, or environmental-are now tracked with increasing regularity. Prior research has revealed that a significant pressure of economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
1
7
1
3
Order By: Relevance
“…ROE influence on PBV, so hypothesis 14 was accepted. These findings supported Mardiati et al (2012) but in contrary to research conducted by Arafat et al (2012) who proved return on equity did not affect the firm value.…”
Section: Discussioncontrasting
confidence: 47%
“…ROE influence on PBV, so hypothesis 14 was accepted. These findings supported Mardiati et al (2012) but in contrary to research conducted by Arafat et al (2012) who proved return on equity did not affect the firm value.…”
Section: Discussioncontrasting
confidence: 47%
“…The more in-depth the knowledge of the field agricultural mentors/officers is, the higher their performance is. This finding is in line with the research that found a significant positive relationship between the variable knowledge and the variable employee performance (Arafat et al, 2012;Kohansal et al, 2013;Nuryanti et al, 2018;Payal et al, 2019;Rizan et al, 2020). As conveyed by Palumbo et al (2005), knowledge contributes a more significant variance in performance improvement.…”
Section: Resultssupporting
confidence: 88%
“…When it comes down to field agricultural mentors/officers, Sumardjo (2008) opines that field mentors/officers' competency is the characteristic attached to a mentor/officer that determines his/her performance effectiveness in assuming the field agricultural mentorship missions. Employees must have high competencies in order to be able to respond to changes in the environment and thus improve performance (Arafat et al, 2012;Sabuhari et al, 2020). The higher the employee competency is, the higher the organizational performance is, and the lower the employee competency is, the lower the organizational performance is (Suharno & Despinur, 2017;Rizan et al, 2020).…”
Section: Competencymentioning
confidence: 99%
“…Joseph (2016), in his research results show that the disclosure of corporate social responsibility influences the value of the firm. Results were also supported by research Arafat, et al (2012). H5: Corporate social responsibility a significant effect on the value of the firm Buzzle and Gale (1987), the size of the company's positive effect on the company's performance means that with increasing size of the company, the company increasingly able to manage economic resources properly, then cause a value of the firm increases.…”
Section: Issn: 1693-5241 181mentioning
confidence: 61%